SKILL DEVELOPMENT PROCESS IN RAJESTHAN-A LITERATURE REVIEW (International Journal of Food and Nutritional Sciences, 2022)
Young people are a valuable human resource for growth, vital agents of social change, and adriving force for both technological and economic progress. However, making use of theseresources is not as simple as one might think. The three primary goals of sustainableagriculture development are the maintenance of existing ways of life, the expansion ofeconomic opportunity, and the protection of the natural environment. Therefore,sustainability is built on the premise that we must meet our wants without risking the abilityof future generations to satisfy their own needs. This is the foundation of the concept ofsustainability. As a result of this, it is very necessary to demonstrate responsible managementof both natural and human resources. The fact that a significant portion of India's populationis of working age is one of the country's many advantages. Because unemployment is just oneof the many challenges that the Indian economy must contend with, the National SkillDevelopment Cooperation was founded in order to address the issue of skill development ona national level. The efforts of the NSDC to improve people's job prospects and lift them outof poverty have made a significant dent in India's economic challenges. In view of theexpanding population and the considerable skill gaps that have been uncovered by a numberof research inquiries, it is essential to have an answer to the question of whether or not thistalent deficiency is being addressed and replaced. This training's success may be attributed,in large part, to the fact that it focuses on commercial topics, as requested by the responders.It is necessary to acknowledge the need for training in order to increase the retention ofpreviously gained information and to encourage better socioeconomic development withincommunities. Additionally, it is necessary to update training materials in line with therequirements and attitudes of trainee participants.